Study of Activation Energy in Soil through Elastic Wave Velocity and Electrical Resistivity. Issue 6 (8th June 2017) - Lee, Jong-Sub; Byun, Yong-Hoon; Yoon, Hyung-Koo
Abstract : Core Ideas: The Arrhenius equation was applied to predict geophysical properties. Elastic and electromagnetic waves were selected. The activation energy exhibited a nonlinear curve. The elastic wave velocity and electrical resistivity of a medium are affected by changes in temperature, which can cause phase changes. The objective of this study was to predict the activation energy based on the Arrhenius equation using the elastic wave velocity and electrical resistivity. Sand with a degree of saturation of 40% was chosen as the medium; the characterization varied during freezing and thawing mechanisms. Silt was added to create a sand–silt mixture to observe the application of the Arrhenius equation under various soil conditions. The compressional wave velocity and shear wave velocity were measured using a piezo disk element and bender element. Four electrodes were used to measure the electrical resistivity of the soil. The temperatures were varied from 10 to −10°C. A thermocouple was installed in the specimen to accurately measure the temperature. The activation energy, which is a crucial parameter in the Arrhenius equation, was calculated using the relationship between the temperature and output values. The activation energies based on the elastic wave velocity and electrical resistivity exhibited different ranges due to the various factors causing chemical reactions in the final products. This study demonstrates that it is possible to predict the activation energy using elastic waves and electrical resistivity during temperature changes.